Editorial: Intercropping Systems in Sustainable Agriculture - Mazzafera, Paulo; Favarin, José Laércio; Andrade, Sara Adrián López de (Frontiers in Sustainable Food Systems, 2021)
In this editorial, we review the articles published in the RT Intercropping Systems in Sustainable Agriculture